Integration of Islamic Economics with the Real Sector: A Systematic Literature Review (SLR) 2020–2025 - Mohamad Ali; Muammar Zulfiqri (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study aims to analyze the factors hindering the integration of Islamic economics with the real sector and to identify mechanisms that can strengthen their linkage. The method employed is a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines, analyzing 47 articles from Scopus and Web of Science-indexed international journals published between 2020 and 2025. The findings identify three main clusters of barriers: institutional barriers within Islamic financial institutions characterized by the dominance of murabahah financing at 60 percent and minimal equity-based instruments; barriers at the real sector level including low Islamic financial literacy averaging 28–34 percent and disproportionate collateral requirements; and macro-structural barriers stemming from suboptimal regulatory frameworks and persistent asymmetric information problems. The study also finds that Islamic fintech holds transformative potential yet its penetration remains below 12 percent, while productive ZISWAF instruments have been proven to increase beneficiary income by up to 47 percent but have not yet reached optimal scale. Cross-country comparative analysis reveals that successful integration is determined by an integrated enabling ecosystem encompassing regulation, institutional innovation, literacy, and digital infrastructure. This study concludes that the required solutions are multi-level and multi-stakeholder in nature, rooted in the maqashid syariah framework